Nanoindentation measurement on interstitial and osteon of bone with osteogenesis imperfecta-type III - Azizan, Nurul Azira; Basarudin, Khairul Salleh; Mat Som, Mohd Hanafi; Khan, S.F.; Sulaiman, A. Razak; Awang, Shukrimi (Zibeline International Publishing Sdn. Bhd., 2019)
"Osteogenesis imperfecta (OI) is one of the genetic disorder which was characterized by bone fragility. Previous studies reported that there are several mechanical properties has been used to investigate the strength of OI bone. However, little data is yet available to describe bone material properties in individuals with this disorder for type III alone. Therefore, the aim of this study is to investigate the mechanical properties in individual with OI bone type III at interstitial and osteon. Bone tissue reduced modulus and hardness were measured by nanoindentation in three specimens with total 40 indents. These properties were compared between osteogenesis imperfecta types III for interstitial and osteonal microstructural regions. Individual with osteogenesis imperfecta type III had higher hardness and reduced modulus at interstitial rather than osteonal bone regions. Overall, the mean and standard deviation of hardness is 0.6 ± 0.11 GPa, while 0.44± 0.06 GPa for osteon. The current study presents the dataset describing the bone material properties in individual with Osteogenesis Imperfecta Type III. Results indicate that intrinsic bone tissues properties were affected by phenotype. Knowledge on the mechanical properties of severity osteogenesis imperfecta may help to assist the model and prevent the fracture risk for those having this disorder."